The Science of Affect: Jacob Riis, Anzia Yezierska and the Modernist Turn in Immigrant Fiction - Farooq, Nihad (American Studies, 2015)
This essay examines the writing of Jacob Riis and Anzia Yezierska to make an argument about the work of immigrant writers as artist-ethnographers, whose observations often straddle the line between science and romance, participant and observer. Riis’s realist, documentary style is paralleled and contrasted with Yezierska’s ethnic avant-gardism to show the very different ways in which both relied on affect – emotion, sentiment, and sensory language – to animate immigrant lives and spaces for a burgeoning American middle class readership. While Riis uses affect to appeal to his readers’ sense of charity and fear – alternating between images of social distance and physical proximity – so that they might be moved to contribute to the amelioration of the living conditions of their encroaching immigrant neighbors, Yezierska instead uses this same kind of affective language and imagery to show that the emotional excess of a community cannot and should not be reined in by scientific and sociological studies that seek to distance and contain immigrant groups. While both writers perform social activism through images and imagistic language, Yezierska’s later writing works to disrupt Riis’s earlier vision of ordered reform by using affect and sentimental language alongside realist conventions and ethnographic practices. This strategic marriage of art and science represents a hybrid modernism that worked to naturalize a new generation of Americans.